Impact of protein-free medium, duration of incubation and temperature on spermatozoa activity post-preparation / Ghofraan A. Ata'Allah - Ghofraan, A. Ata'Allah (2016)
The objectives of this study were to identify factors that could retain the activity of human spermatozoa over extended periods of time, and to establish the efficacy of the synthetic chemically defined protein-free spermatozoa handling and culture media on spermatozoa motility and vitality. Semen samples were obtained following informed consent. In Experiment 1 semen samples were prepared by density gradient centrifugation. The resulting re-suspended pellet was apportioned equally in the commercial protein-containing medium (CPC); minimum essential medium + HSA (MEM) or the synthetic protein-free medium (PFM). In Experiment 2 the motility of spermatozoa held for 24hrs at 4oC, 15oC, 22oC or 37oC in CPC, MEM or PFM media were determined. In Experiment 3 the vitality and viability of human spermatozoa held at room temperature were evaluated at 0hr, 4-7hrs and 24hrs post-wash. There is no difference in the activity of human spermatozoa in the protein-containing or protein-free handling and culture media. There is no significant difference in the spermatozoa motility held at different temperatures for 4-7hrs post-wash, but it was highest at 22oC; likewise after 24hrs the significantly highest motility was noted at 22oC than 37oC, 15oC and 4oC (p<0.05) in all media. The same was true for spermatozoa vitality and membrane integrity at 4-7hrs, but a significant reduction was noted after 24hrs at 37oC (p<0.05). There were no significant changes in the DNA integrity levels when spermatozoa was held at 22oC or 37oC for 4-7hrs or 24hrs in all media. In conclusion the activity of spermatozoa can be successfully retained at room temperature for up to 24hrs without major detriment. The efficacy of the protein-free media is equally efficient as the conventional protein-containing media.